KEJAHATAN TRANSNASIONAL PERMUFAKATAN JAHAT DALAM TINDAK PIDANA JUAL BELI NARKOTIKA GOLONGAN I - Rachmawati, Ananda Noor Eliza (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2023)
This study aims to find out and analysis the regulation of criminal conspiracy in the crime of buying and selling narcotics class I and ASEAN’s efforts to eradicate transnational crimes against narcootics crimes. This research is a normative or doctrinal legal research. This research is prescriptive and applied. The approach used by the author is the statutory approach. The technique for collecting legal material in this study used a literature study technique and the analysis technique for legal material used the deductive syllogistic method. The data in this study were obtained from primary data and secondary data. Based on the results of the research and discussion, it can be concluded that the regulation regarding the act of buying and selling narcotics class I which is carried out by conspiracy is regulated in Article 114 particle (2) of Law Number 35 of 2009 concerning narcotics. However, if the act of buying and selling narcotics class I is carried out by agreement and weighing more than 1 (one) kilogram for plant forms and weighing more than 5 (five) grams for non-plant forms. Then Article 114 particle (2) in conjuction Article 132 particle (1) of Law Number 35 of 2009 concerning narcotics. In dealing with the problem of illicit trafficking of narcotics in the Southeast Asian region, ASEAN member countries already have several forums or forums to deal with problems related to narcotics, including ASOD,AMMDM,AIFOCOM and ASEANAPOL.